Understanding the Escalation статьи in U.S.-Russian Relations during the D. Trump Era: Unpacking the “Split Subject” Phenomenon - A. O. Tsatsurin (Международная аналитика)
Donald Trump’s victory in the 2016 presidential election intensifi ed the divide within American society and the political climate in Washington, causing a signifi cant impact on the relationship between Moscow and Washington. Despite the US political system overcoming the challenges faced during Trump’s presidency, there was also a surge in tensions between the US and Russia. The deterioration of bilateral relations can be attributed to the dysfunctional interagency communication channels and the tightening of sanctions through the CAATSA law. Moscow ultimately shifted its stance from aspiring to normalization to recognizing the likelihood of military-political confrontation. This article presents a hypothesis that comprehensively explains the factors contributing to this shift. The hypothesis underscores the lack of coherence among American political leaders, as four unique interest groups – President Trump, Republican hawks, oppositional bureaucrats, and Democratic Congress members – all contribute to shaping US policy toward Russia. Each group advances its specifi c objectives, sometimes joining forces to bypass the president’s policies. Consequently, a “split subject” phenomenon emerges in US-Russian aff airs. The author concludes that the lack of constructive dialogue with Washington during Trump’s presidency was due to the “split subject.” The victory of J. Biden in the 2020 elections and the alignment of American bipartisan elites amid the Russian-Ukrainian confl ict temporarily shifted this phenomenon to the background. Nevertheless, the author raises the question of whether this “cleavage” might reemerge if Trump or his close associates win the 2024 US presidential election.